76 Health-related quality of life (HRQOL) and school functioning in students with acute sports-related concussion. (9th June 2015) - Chu, Stephanie; Selci, Erin; Morwick, Karissa; Ellis, Michael; Russell, Kelly
Abstract : No evidence-based Return-To-Learn program is available to help students return to school after a concussion. The objective was to examine the relationship between health-related quality of life (HRQoL), symptom severity, and school functioning in students with a sport-related concussion. This prospective case-series was conducted with students (13–18 years) who presented to the Pan Am Concussion Program in Winnipeg, Canada and were diagnosed with an acute sport-related concussion by a neurosurgeon. At each appointment, students completed the Post-concussion Symptom Severity (PCSS) scale, PedsQL 4.0 (physical, social, school, emotional functioning domains) and cognitive functioning. They received a log book to track school attendance. At medical clearance, exit interviews were conducted to examine the impact of their concussion on academics and HRQoL. Fifty-four students (57% male) were diagnosed with an acute-sport related concussion. Students initially presented with median PCSS score of 19 (IQR: 8, 34) and had poorest HRQoL in the physical and cognitive domains. At each medical appointment, PCSS score decreased by 6.3 points (95% CI: −7.6, −4.9). All HRQoL domains significantly improved over time; however, mean cognitive functioning scores remained the lowest at medical clearance (75.0; SD:3.8). There was no significant difference in median days to medical clearance among students who rated their school accommodations as poor (n = 8) compared with those who rated them as good (n = 20) (19 vs. 27 days; p = 0.42). Students missed a median of 7 days of school and returning to Math (16/27, 59%) and Science (14/29, 48%) was the most difficult. Concussion symptoms and all domains of HRQoL improve over time. Yet cognitive functioning scores (attention, remembering, and thinking) remain low after medical clearance and this could affect academic performance. This study provides evidence documenting students' struggles when recovering from their concussion and returning to school. This information can help form a Return-To-Learn program.